(untitled) - Peterson, Brian Neil; (1966-...) (U.S.A, 2014)
Peterson engages the identities and provenances of the authors of the various `editions` of the Deteronomistic History. Peterson asks where we might locate a figure with both motive and opportunity to draw up a proto-narrative including elements of Joshua, Judges, Samuel, and the first part of 1 Kings. Peterson identifies a particular candidate in the time of David who qualified to write the first edition. He then identifies the particular circle of custodians of the Deuteronomistic narrative and supplies successive redactions down to the time of Jeremiah.
Keywords: Religion -- Biblical Studies -- Old Testament